2004
DOI: 10.1111/j.1399-0004.2004.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and obesity‐related factors in Prader–Willi syndrome: Comparison with obese subjects

Abstract: Prader-Willi syndrome (PWS), the most common genetic cause of marked obesity in humans, is usually due to a de novo paternally derived chromosome 15q11-q13 deletion or maternal disomy 15 [(uniparental disomy (UPD)]. Obesity is due to energy imbalance, but few studies have examined fat patterning and obesity-related factors in subjects with PWS (deletions and UPD) compared with subjects with simple obesity. We examined for differences in fatness patterning and lipid, leptin, and glucose and insulin levels in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
81
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 28 publications
15
81
2
Order By: Relevance
“…The obesity in PWS affects both the trunk and the limbs, 28 but a greater proportion of the abdominal fat is localized subcutaneously rather than around the visceral organs. 14,27 Our results are consistent with the hypothesis that excessive visceral, rather than subcutaneous, adiposity is particularly likely to be associated with decreased production and circulating levels of adiponectin. This could explain why PWS subjects with a greater percentage body fat have higher adiponectin levels, and why, in PWS individuals, there is a significant negative correlation between plasma adiponectin and waist-to-hip ratio, although Hoybye et al 15 did not report a significant negative correlation between adiponectin levels and waistto-hip ratios in their PWS subjects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The obesity in PWS affects both the trunk and the limbs, 28 but a greater proportion of the abdominal fat is localized subcutaneously rather than around the visceral organs. 14,27 Our results are consistent with the hypothesis that excessive visceral, rather than subcutaneous, adiposity is particularly likely to be associated with decreased production and circulating levels of adiponectin. This could explain why PWS subjects with a greater percentage body fat have higher adiponectin levels, and why, in PWS individuals, there is a significant negative correlation between plasma adiponectin and waist-to-hip ratio, although Hoybye et al 15 did not report a significant negative correlation between adiponectin levels and waistto-hip ratios in their PWS subjects.…”
Section: Discussionsupporting
confidence: 88%
“…26 People with PWS may be less likely to develop diabetes mellitus or the metabolic syndrome than nonsyndromic people with comparable obesity. 14,27 Although our two groups of subjects (PWS and simple obesity) were matched for BMI, PWS subjects had a greater percentage body fat mass. The obesity in PWS affects both the trunk and the limbs, 28 but a greater proportion of the abdominal fat is localized subcutaneously rather than around the visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the two groups were also matched for central adiposity and insulin resistance without specific selection of control subjects. Although our PWS cohort might seem unusual, as a lower visceral fat mass and preserved insulin sensitivity has been reported previously (Brambilla et al, 1997, Goldstone et al, 2001, Goldstone et al, 2004, Goldstone et al, 2005, Talebizadeh and Butler, 2005, Kennedy et al, 2006, Theodoro et al, 2006, Haqq et al, 2010and Sode-Carlsen et al, 2010, other investigators recently reported similar observations to ours, i.e. obese children and adults with PWS having the same amount of visceral fat mass, the same degree of insulin resistance and a similar prevalence of metabolic syndrome compared to carefully weight-matched obese subjects Butler, 2005 andBrambilla et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…2D). The postprandial meal response of GLP-1[active] was not statistically (Talebizadeh and Butler, 2005;Brambilla et al, 2010). The present study was not designed to compare body composition and fat distribution between PWS and obese subjects, as a larger cohort would be needed to that end.…”
Section: Discussionmentioning
confidence: 99%
“…PWS individuals may be less likely to develop T2DM than non-syndromic subjects with comparable obesity. In fact, the lower fasting insulin and HOMA-IR were shown in not only PWS children but also PWS adults 5,6) . However, recent study suggested further investigation with hyperinsulinemic-euglycemic clamp due to failure to reprove this identification 7) .…”
Section: Altered Glucose Metabolism In Pwsmentioning
confidence: 99%